The relationship between anxiety and cardiometabolic risk factors in adolescents with obesity: propensity scores - Villasis-Keever, Miguel Angel; Zurita-Cruz, Jessie Nallely; Pichardo-Estrada, Areli Zulema; Mazón-Aguirre, Wendy Alejandra (Frontiers in Endocrinology, 2025)
BackgroundIt has been described that there is a relationship between metabolic health and anxiety.ObjectiveTo determine the relationship between anxiety and metabolic syndrome, as well as cardiometabolic risk factors, in adolescents with obesity.MethodsWe conducted a comparative cross-sectional study of adolescents with obesity between January 2019 and December 2022. In each patient, we recorded somatometric measurements, lipid profiles, and serum insulin levels. Anxiety was measured using the Spence Children’s Anxiety Scale. Participants were divided into those with and without anxiety. Patients with anxiety were matched to patients without anxiety using propensity scores based on z-score body mass index (zBMI). Mann–Whitney U tests and χ2 tests were used.ResultsOf the 564 adolescents, 32.6% (n = 184) suffered from anxiety. In the overall study population, no differences in biochemical and cardiometabolic parameters were observed between the adolescents with and without anxiety prior to adjusting the groups based on zBMI. After matching using their zBMI, we found that the adolescents with anxiety had higher serum uric acid levels (5.9 mg/dl vs. 5.4 mg/dl, p = 0.041), an increased incidence of metabolic syndrome (39.1% vs. 15.9%, p = 0.002), hyperglycemia (21.7% vs. 8.6%, p = 0.020), and lower HDLc (67.3% vs. 34.7%, p < 0.001), than those without anxiety. Girls with anxiety had a higher proportion of cardiometabolic risk factors compared to those without anxiety.ConclusionsAdolescents with obesity and anxiety had higher cardiometabolic risk factors than those without anxiety.